ANALISIS DAMPAK SENTIMEN INVESTOR TERHADAP RETURN SAHAM MENGGUNAKAN EGARCH: STUDI KASUS PADA BANK RAKYAT INDONESIA, TBK. - Suhendro Suhendro; Purnama Siddi; Yuli Chomsatu Samrotun (Jurnal Pendidikan Ekonomi dan Akuntansi, 2023)
Volatility reflects fluctuations in stock prices within a certain period. The purpose of this study was to examine the effect of market volatility and psychological sentiment on company stock return. This study uses a sample of PT Bank Rakyat Indonesia, Tbk as a company with good performance and a large number of investors on the Indonesia Stock Exchange. This study uses multiple regression based on daily data for 2015-2021 analyzed using Exponential GARCH. This study reveals that market volatility indicated by the LQ45 index has a significant effect on stock return volatility. Meanwhile, market sentiment as measured by index volatility has no effect on stock return.Keywords: volatility; psychological sentiment; stock prices